Analysis of FreeRTOS Overheads on Periodic Tasks - Miranda, Bruno Dourado; Oliveira, Rômulo Silva de; Carminati, Andreu (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2021: Anais do XX Workshop em Desempenho de Sistemas Computacionais e de ComunicaçãoDO - 10.5753/wperformance.2021.15728, 2021)
Real-Time Operating Systems (RTOS) have their own modules that need to be executed to manage system resources and such modules add overhead to task response times. FreeRTOS is used for experimental purposes since its is a widely used open-source RTOS. This work presents the investigation of two important sources of overhead: Function Tick, a FreeRTOS time marker, and the Context Switch between tasks. In this paper we also describe a model for reducing Tick analysis pessimism due to its temporal variation. Experiments measuring the execution time of Tick and Context Switch on ARM-Cortex M4 microprocessor were made to present the Best-Case Execution Time and the Worst-Case Execution time within a periodic task scenario. Measurements are used to validate the analytic models.